Effect of Bamboo Salt on Inhibition of Adhesion of Candida albicans to Denture Acrylic Resin: An in vitro Study - Keerthika Natarajan; Murugesan Krishnan; Suganya Srinivasan; Gowtham Venkat; Muthukumar Balasubramaniam (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Adhesion of Candida albicans on denture surfaces is one of the main aetiology of denture stomatitis. Currently, chemical disinfectant agents have been employed to prevent its adhesion on the denture surface. However, due to its harmful effects on the physical properties of the denture material there has been a lookout for a natural product as a replacement. Aim: Investigate the effects of Bamboo Salt Solution (BSS) on inhibition of adhesion of Candida albicans (C. albicans) to denture acrylic surface. Materials and Methods: Transparent acrylic strips were pretreated with bamboo salt at concentration of 5, 10, 20 w/v %, normal saline (negative control) and 0.2% chlorhexidine gluconate (positive control) for 30 minutes followed by inoculation with C. albicans (107 cells/mL). Adherent yeast cells were then counted under microscope at 40X magnification in 20 randomly selected fields on each strip after staining with crystal violet. The statistical significance was calculated by Kruskal-Wallis and Mann-Whitney non-parametric tests at a significance level of p<0.05. Results: The mean percentage of inhibition after pretreatment with 5%, 10% and 20% of the extract were 43.9%, 65.7% and 86.7% respectively. Pretreatment with BSS significantly reduced the adhesion of C. albicans to acrylic surfaces in a dose dependent manner. Conclusion: This observation indicates that BSS has an inhibitory effect on the ability of C. albicans to adhere to denture acrylic and could be employed as a denture disinfecting agent for preventing denture stomatitis.